PERCERAIAN DAN KEKERASAN TERHADAP ISTRI DI KOTA JAMBI - Rasito Rasito (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2019)
This writing is aimed at elaborating the forms of violation against woman (wives) in the case of divorce in Jambi City. This research is exploratory. In this case, divorces in Jambi are predominantly dominated by sue-divorced, cerai gugat (67.975%). From the research, uncovered some facts that the dominant forms of violationos are: physical violatios (37.255 %), psychological and emotional violations (88.235%), and sexual violations (0.64%). All kinds of the above violations are interconnected into each other in causes. The law enforcement for equality and protection on the woman are still very far from perfedct. From this view, it is worth socializiing the gender equality to the society as well as to the law practitioner and to the law-decision maker.